Integrating gender in aquaculture and small scale fisheries agri-food systems research: Pitfalls, principles and practical ways forward - Newton, Julie (CGIAR Collaborative Platform on Gender Research, 2019)
Presented by Julie Newton (KIT Royal Tropical Institute), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.